2009 Computation World: Future Computing, Service Computation, Cognitive, Adaptive, Content, Patterns 2009
DOI: 10.1109/computationworld.2009.8
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Facial Animation Production through Artistic Inquiry

Abstract: Studies into dynamic facial expressions tend to make use of experimental methods based on objectively manipulated stimuli. New techniques for displaying increasingly realistic facial movement and methods of measuring observer responses are typical of computer animation and psychology facial expression research. However, few projects focus on the artistic nature of performance production. Instead, most concentrate on the naturalistic appearance of posed or acted expressions. In this paper, the authors discuss a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…This method consists of four stages of animation practice; planning, action, post-action, and evaluation. The cycle is repeated several times, with each full cycle generating new iterations of animation 21 . The goal of the practitionerresearcher is to investigate the overall effectiveness of each CEE applied to a range of emotional expression animations.…”
Section: Inquiry Cycle Methods Of Animation Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…This method consists of four stages of animation practice; planning, action, post-action, and evaluation. The cycle is repeated several times, with each full cycle generating new iterations of animation 21 . The goal of the practitionerresearcher is to investigate the overall effectiveness of each CEE applied to a range of emotional expression animations.…”
Section: Inquiry Cycle Methods Of Animation Productionmentioning
confidence: 99%
“…Effectiveness is evaluated based on; how artistically intuitive a CEE is (i.e., whether the practitioner would naturally opt to use the CEE) how difficult a CEE is to apply to a character using creative animation practices, how clear and authentic the resulting animation is, and how a CEE may be appropriately used in various contexts (e.g., the narrative context, the emotional context, in relation to the character's personality, etc). These artistic considerations are explored using an array of practice-based tools (including sketchbooks and an artist's journal) which in turn can be used to generate and convey performative data 21 .…”
Section: Inquiry Cycle Methods Of Animation Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Practice-based research using this framework demonstrated that experimentation with EEC could affect the animator's interpretation of expression authenticity, clarity, and context (Sloan et al, 2009(Sloan et al, , 2010. In addition, tests of observer perception demonstrated that manipulation of EEC can impact on audience interpretation of expression authenticity.…”
Section: Emotional Expression Choreographymentioning
confidence: 94%
“…Traditional animators have a strong foundation in the observation of nature, but also hold tacit knowledge regarding the procedures for successfully imitating -rather than replicating -life. Previous research has shown that an arts-based approach to facial animation research can be adopted to generate detailed predictions regarding the clarity and authenticity of dynamic expressions (Sloan et al, 2009). Subsequent studies have demonstrated that the predictions of artistically produced configurations of facial movement -termed emotional expression choreography (EEC) -can be verified empirically through tests of observer perception (Sloan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%